A Novel Water‐Soluble Fluorescence Probe with Wash‐Free Cellular Imaging Capacity Based on AIE Characteristics. Issue 10 (21st March 2017) - Qian, Yunxia; Liu, Hongmei; Tan, Haijian; Yang, Qingmin; Zhang, Shuchen; Han, Lingui; Yi, Xuegang; Huo, Li; Zhao, Hongchi; Wu, Yonggang; Bai, Libin; Ba, Xinwu
Abstract : A novel water‐soluble fluorescence probe (P3) with wash‐free cellular imaging capacity and pH‐controlled fluorescence response based on aggregation‐induced emission characteristics is designed and synthesized via a facile one‐pot method. Wash‐free cellular imaging and photoluminescence (PL) spectra show that theP3 enjoys high signal‐to‐noise ratio for concentrations up to 50 μg mL −1 and special pH‐responsive fluorescence, which have a promising application in biological detection. Abstract : A potential real‐time imaging water‐soluble fluorescent polymer (P3 ) is facilely prepared via one‐pot method. ForP3, tetraphenylethene unit serves as the fluorescent unit, poly(acryloyl ethylene diamine) (a kind of polyelectrolyte) with specific degree of polymerization acts as water‐soluble part. 1 H‐NMR, gel permeation chromatography (GPC), UV‐vis spectroscopy, photoluminescence (PL), and confocal laser scanning microscopy are undertaken to characterize the structure and property ofP3 . The results of wash‐free cellular imaging show that the signal‐to‐noise ratio is high as the concentration ofP3 is 50 μg mL −1 . In addition, the pH‐responsive and Cd 2+ ‐responsive are also investigated in this paper. The results coming from pH‐responsive show thatP3 solution displays significant fluorescence under near neutral. And the result from the cellular imaging shows that intracellular fluorescence intensity enhances with the augment of concentration of Cd 2+, which reveals thatP3 can give a hint to resolve the dilemma of traditional fluorescent dyes used as living cellular fluorescent probe.